2001
DOI: 10.1159/000047693
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Fibrillation during Off-Pump Coronary Artery Bypass Grafting: Transcranial Doppler and Clinical Findings

Abstract: A 73-year-old male developed ventricular fibrillation which lasted for 2 min and 24 s, during off-pump coronary artery bypass grafting. Cerebral hemodynamics were assessed by continuous transcranial Doppler monitoring. Ventricular fibrillation resulted in an immediate fall in cerebral blood flow velocities to almost zero with only slight fluctuations. This was then followed by a pronounced reactive hyperperfusion. Cerebral magnetic resonance imaging examinations and detailed neurological and neuropsychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…We did not find similar results in the group without cardiopulmonary bypass, in which manipulation of the heart during off-pump surgery has the potential to cause episodes of hemodynamic instability and critical cerebral hypoperfusion without hypothermic protection. 25 Previous randomized trials of on-pump versus off-pump bypass surgery have failed to demonstrate significant independent effects of cardiopulmonary bypass on patientreported health status. [26][27][28] In the present study no independent statistical effect was observed of new postoperative lesions on self-reported health.…”
Section: Table 2 Baseline and 3-month Physical And Mental Health Summary Scores On The Basis Of Cerebral Mri Classificationmentioning
confidence: 99%
“…We did not find similar results in the group without cardiopulmonary bypass, in which manipulation of the heart during off-pump surgery has the potential to cause episodes of hemodynamic instability and critical cerebral hypoperfusion without hypothermic protection. 25 Previous randomized trials of on-pump versus off-pump bypass surgery have failed to demonstrate significant independent effects of cardiopulmonary bypass on patientreported health status. [26][27][28] In the present study no independent statistical effect was observed of new postoperative lesions on self-reported health.…”
Section: Table 2 Baseline and 3-month Physical And Mental Health Summary Scores On The Basis Of Cerebral Mri Classificationmentioning
confidence: 99%
“…However, during boffpumpQ surgery, there is more manipulation of the heart which may precipitate serious cardiac arrhythmias, with a subsequent fall in cerebral perfusion pressure. TCD monitoring will then immediately detect a significant fall in MCA blood flow velocities, which will enable the surgical team to take immediate corrective measures [15] (Fig. 4).…”
Section: Cerebral Hemodynamicsmentioning
confidence: 99%